Respon Eksplan Tunas Homalomena rubescens terhadap Kualitas Cahaya dan Efeknya pada Pengayaan Metabolit Sekunder - Zikra Lareta Putri; Zozy Aneloi Noli; M Idris (Vegetalika, 2026)
Homalomena rubescens (Araceae) is an ornamental plant known for its distinctive aroma from the roots, rhizomes, and leaves. Species of the genus Homalomena are rich in secondary metabolites with potential pharmaceutical applications, including anti-Alzheimer, anti-inflammatory, antibacterial, and antioxidant properties. Enrichment of secondary metabolites in plants can be achieved through environmental modifications, e.g. light quality. In vitro techniques, particularly the use of light-emitting diodes (LEDs), are valuable for studying the effects of light quality. This study aimed to evaluate the effects of monochromatic light (blue; 400-500 nm and red; 600-700 nm) on the growth and secondary metabolite enrichment in H. rubescens shoots. Additionally, the response of two Homalomena species (H. rubescens and H. pendula) to callus induction under different light treatments was assessed. Polychromatic light (white; 400-700 nm) served as positive control, while total darkness acted as the negative control. Light treatments were applied during a 12-hour photoperiod. Results showed that red light enhanced shoot initiation, leading to a higher number of shoots, while blue light promoted increased shoot height and resulted in darker green shoots. Phytochemical analysis indicated that blue light enhanced the accumulation of flavonoids, phenols, and terpenoids. Additionally, blue light improved callus induction in both species. These findings suggest that red light is more effective in promoting shoot growth, while blue light supports secondary metabolite enrichment.